INVESTMENT DECISIONS, FUNDING DECISIONS AND ACTIVITY RATIOS ON FIRM VALUE IN INDONESIA - Listyawati, Reni; Galang Wicaksana, Fandi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to find out how decisions about investment, funding, and activity ratio affect the value of manufacturing companies on the Indonesia Stock Exchange. The population of this study consisted of 179 manufacturing businesses that are listed on the Indonesia Stock Exchange. The study spans the years 2015 to 2019.Thirty manufacturing companies were used as samples, and the purposive sampling method was used for the sampling. The method of analysis employed is multiple linear regression. The results show that firm value is affected simultaneously by funding decisions, investment decisions, and activity ratio decisions. Firm value is unaffected by funding decisions, activity ratios are unaffected by funding decisions, and investment decisions are somewhat affected by funding decisions.